Electromagnetic Wave scattering with special spatial lattices of magnetodielectric spheres - Kozar, A. I. (New York, N.Y. Begell House, 2004)
A problem solution of electromagnetic wave scattering with special compound lattices of resonance spheres has been considered, their spatial distribution has been subjected to a geometric progression. Expressions for the scattered fields have been obtained.
Keywords: magnetodielectric spheres; electromagnetic wave